Trends in tracheostomy placement after out-of-hospital cardiac arrest - Francisco Gallegos-Koyner; Nelson Barrera; Ricardo M. Carvalhais; David H. Chong; Anica Law; Ari Moskowitz (Resuscitation Plus)
Purpose: Out-of-hospital cardiac arrest (OHCA) is a major public health burden. The purpose of this study was to assess the incidence of tracheostomy placement after OHCA and to evaluate trends over time and cost. Methods: Using the National Inpatient Sample data 2016–2021, we examined a weighted sample of adults admitted after OHCA who underwent mechanical ventilation within the first 24 h of arrival and had an admission longer than 24 h. The primary outcome of interest was incidence of tracheostomy placement after cardiac arrest. Secondary outcomes of interest included hospitalization costs, days to tracheostomy placement, length of stay and discharge disposition. Results: A total of 47,550 admissions fulfilled the inclusion criteria. Of those, 1,450 (3.0%) patients received a tracheostomy during their hospitalization. There was no change in the incidence of tracheostomy placement over the analyzed years. Median hospitalization costs for patients with OHCA who received a tracheostomy were $96,038 (IQR= $66,415−$148,633). Hospitalization costs steadily increased over the analyzed years, from $83,668 in 2016 to $109,032 in 2021. Median days to tracheostomy placement was 11 days (IQR = 8–15) and median length of stay of patients with OHCA and tracheostomy was 23 days (IQR = 16–36). There was no significant change over the years in days to tracheostomy placement or in length of stay to explain the increase in hospitalization costs. Among patients with tracheostomy, 76.2% were discharged to a Skilled Nursing Facility, 13.8% died, 4.8% were discharged to a short-term hospital, and 5.2% were discharged home. Conclusions: An estimated 3.0% of patients who are admitted to the hospital after OHCA and require mechanical ventilation will receive a tracheostomy. Between 2016–2021 the rates and timing of tracheostomy placement remained stable in patients admitted with OHCA. However, we observed a rise in hospitalization costs associated with patients admitted for OHCA.